Urinary calcium and bone mineral density in children with nephrotic syndrome treated with glucocorticoids - Patil, Sharanagouda; Reddy, Sanjeev (International Journal of Contemporary Pediatrics, 2020)
Background: Mainstay of therapy in the idiopathic nephrotic syndrome is glucocorticoids. Glucocorticoid induced osteoporosis is considered as most prevalent type of secondary osteoporosis. Only limited studies are conducted in tropical nations. Therefore our study is undertaken with objectives to evaluate Glucocorticoid therapy impact on bone health in Nephrotic Syndrome (NS) children by 2 different tools, namely urinary calcium and bone mineral density (BMD) by Quantitative ultrasound (QUS) and compare both the tools. Methods: Total 42 children with NS who completed minimum 12 weeks of Glucocorticoid therapy (6 weeks of daily regimen and minimum 6 weeks of alternate day regimen) were subjected to 24 hour Urinary calcium and Bone Mineral density by QUS at Tertiary health centre, Kalaburagi. Results: Out of 42 cases, 45.2 % had Osteopenia and 2.4% had osteoporosis, so 47.6% of them had BMD measured by QUS. Hypercalciurea was seen in 10 out of 42 cases (23.8%). In normal BMD group only 0.5% had hypercalciurea, Osteopenia group had 47.4% of cases and all osteoporosis group had hypercalciurea. Conclusions: Present study data concludes that children with NS treated with Glucocorticoids are at risk of Negative impact on bone health. Though both the tools detect impact of Glucocorticoids on bone health, BMD by QUS has better rate then urinary calcium in detecting negative effect of Glucocorticoid on bone health. As BMD by QUS decreases, Urinary calcium increases reflecting inverse relation between them.